The relationship of the ethnic structure and Belarusian labor migration in Russian regions - Anatoly G. Zlotnikov (Наука. Культура. Общество, 2020)
The article analyzes the trends in the change of the size of the Belarusian ethnic group in the ethnic struc- ture of the regions of Russia. Their interrelation with tendencies of the Belarusian labor migration in the Russian labor market is traced. The role of Belarusian labor migration as a donor of economic and social processes in the Russian Federation is characterized. The conflicting interests of the Belarusian and Russian States in approaches to migration policy are considered.